Notes for a martyrial culture - Rosado Calderón, Juan (Razón y fe, 2022)
The building of a new culture is an inescapable challenge for Christians in the present historical moment. But in fidelity to the spiritual tradition, such a task will have to begin at the very sources of being Christian, as an action derived from the cult that makes the person grow. As a requirement for Christian youth, in this article I will explore the features of this culture conceived as a new community presence, as an initiation to the mystery, as a unique way of being and thinking, and, therefore, of communicating the Christian truth in a martyrial way.